Comparison of intrathecal Nalbuphine and Clonidine as adjuvants to Bupivacaine heavy for spinal anesthesia in elective infraumbilical surgeries in adult patients – a prospective study - Girish, BK; Manjula, BP; Akshay, HM; Shivakumar, KG; Navakanth, D; Nandi Vinayaka , B (Asian Journal of Medical Sciences, 2022)
Background: Post-operative analgesia is a major problem associated with relatively short duration of action of spinal-anesthetics. Intrathecal adjuvants can prolong the duration of analgesia giving better success rate & patient satisfaction. Aims and Objectives: To assess the duration of postoperative analgesia with intrathecal bupivacaine supplemented with either nalbuphine or clonidine as adjuvants and also to assess the time of onset, maximum level and duration of sensory and motor blockade, and any postoperative complications. Materials and Methods: Following institutional ethical committee approval 60 patients scheduled for elective infra umbilical surgeries duration of less than 2 hours, under spinal anesthesia, were included in this prospective randomized interventional study. Patients were randomly allocated to one of two groups into Group-N received 2.5 ml of 0.5 % hyperbaric bupivacine + 0.5ml of nalbuphine (0.4mg). Group-C received 2.5 ml of 0.5% hyperbaric bupivacine + 0.5 ml of clonidine (30 μg). The onset of sensory and motor blockade, duration of sensory and motor blockade, two-segment regression time from highest level of sensory blockade, and duration of analgesia was recorded. Results: Total duration of postoperative analgesia was significantly higher in group-C(351.00±31.00 min) than in group-N(256.00±8.14 min). Though the mean time for onset of sensory and motor block among both groups was not significantly different, the mean time for complete sensory and motor recovery was significantly longer in Group-C than Group-N. Conclusion: Intrathecal clonidine has more prolonged analgesia and motor blockade compared to nalbuphine, and hence clonidine can be preferred over nalbuphine as an intrathecal adjuvant.